Comparison between two tomographic sections in the diagnosis of external root resorption - Cláudio Afonso Lermen; Gabriela Salatino Liedke; Heloísa Emília Dias da Silveira; Heraldo Luis Dias da Silveira; Alessandro André Mazzola; José Antônio Poli de Figueiredo (University of São Paulo, 2010)
OBJECTIVES: To assess the accuracy of coronal and sagittal CT sections to detect cavities simulating root resorption. MATERIAL AND METHODS: 60 mandibular incisors were embedded in plaster bases, and cavities with 0.6, 1.2 or 1.8 mm in diameter and 0.3, 0.6 or 0.9 mm in depth (small, medium and large cavities) were drilled on the buccal surfaces with high-speed round burs with diameters of 0.6, 1.2 and 1.8 mm to simulate external inflammatory root resorption. Simulations in the cervical, middle and apical thirds of each tooth root were made randomly. The Dental Scan software was used to obtain 1-mm-thick axial images from direct scanning, which were reconstructed in the coronal and sagittal planes using 3D software (Syngo FastView). Each series was loaded into the software. Fourteen images of each tooth were reconstructed in the coronal plane and 14 in the sagittal plane. A total of 1,652 images were obtained for analysis. Series information, tooth number and the plane reconstructed were stored. The images generated were saved on a CD-ROM together with the visualization software (Syngo FastView). Images were analyzed by a previously calibrated blinded, radiologist. Cochran's Q test was conducted separately for each region analyzed followed by pair-wise comparison by the McNemar test (p=0.05). RESULTS: No statistically significant difference (p>0.05) was observed in the diagnosis of simulated resorption between the apical, middle, and coronal thirds. When the axial plane was assessed separately, diagnoses were statistically different (p<0.05) among the three root thirds. The apical third differed significantly (p<0.05) from the cervical and middle thirds. Diagnostic errors were more often observed in the apical third compared to the cervical and middle thirds. Mid-sized cavities revealed no statistically significant differences (p>0.05) between planes, irrespective of the third in which the resorptions were located. CONCLUSION: When tomographic sections are requested for the diagnosis of buccal or lingual external root resorption, sagittal sections afford the best image characterization of the resorption process.